2021
DOI: 10.3390/ijms22084098
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of NEIL3 Enhances the Chemotherapy Resistance of Prostate Cancer

Abstract: Acquired treatment resistance is an important cause of death in prostate cancer, and this study aimed to explore the mechanisms of chemotherapy resistance in prostate cancer. We employed castration-resistant prostate cancer (CRPC), neuroendocrine prostate cancer (NEPC), and chemotherapy-resistant prostate cancer datasets to screen for potential target genes. The Cancer Genome Atlas (TCGA) was used to detect the correlation between the target genes and prognosis and clinical characteristics. Nei endonuclease VI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Elevated neuroendocrine markers and docetaxel resistance are the two notable features of NEPC [ 5 , 48 ]. We then tested whether e2e4 affects these features.…”
Section: Resultsmentioning
confidence: 99%
“…Elevated neuroendocrine markers and docetaxel resistance are the two notable features of NEPC [ 5 , 48 ]. We then tested whether e2e4 affects these features.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Rolseth et al found that compared to control mice, cancer predisposition or increased spontaneous mutation frequencies were not observed in NEIL1/2/3 DNA glycosylases-deficient mice, indicating that NEIL1/2/3 might be essential in cancer prevention [ 22 ]. The cancer-promoting effects of NEIL3 have been proven in multiple cancers, including prostate, liver, and breast cancers [ 17 , 21 , 23 ]. Our results indicate that NEIL3 promotes NSCLC cell proliferation, invasion, and migration partially by regulating the classic PI3K/AKT/mTOR signaling pathway; thus, it might be a promising therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors with overexpressed NEIL3 are often accompanied by anomalous expression levels of homologous recombination genes (BRCA1/2) and mismatch repair genes (MSH2/MSH6) [ 16 ]. Wang et al found that NEIL3 promotes prostate cancer cell proliferation and cisplatin resistance by inhibiting the phosphorylation of ATR and ATM serine/threonine kinase [ 17 ]. Meanwhile, Klattenhoff et al found that the loss of NEIL3 markedly enhances replication-associated double-strand breaks and enhances sensitivity to ATR inhibitors in glioblastoma cells [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the loss of NEIL3 in prostate cancer could inhibit cell apoptosis and cell cycle arrest under cisplatin treatment ( Wang et al, 2021 ). UNG rs246079 G/A might contribute to a decreased risk of esophageal cancer and an increased risk of cervical carcinoma ( Yin et al, 2014 ; Ye et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%